In-season training load quantification of one-, two- and three-game week schedules in a top European professional soccer team - Oliveira, R.; Brito, J.; Martins, A.; Mendes, B.; Calvete, F.; Carriço, S.; Ferrazce, R.; Marques, M. C. (Physiology & Behavior, 2019)
• Similar s-RPE for one-, two- or three-game weeks microcycles • Lower values in the last day prior to a match, for all microcycles and variables • Higher value of training duration in one- or two-game than three-game weeks • Week with two official matches revealed significantly greater values of CK.